2014
DOI: 10.1177/1534765613496647
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes of Mexico’s drug war in Ciudad Juárez: A pilot study among university students.

Abstract: During the most intense period of armed conflict related to the drug trade in Mexico, forty students attending the Universidad Autónoma de Ciudad Juárez (UACJ) in Ciudad Juárez, Chihuahua, Mexico, were surveyed in this pilot study for symptoms of depression, anxiety and post-traumatic stress using the Harvard Trauma Questionnaire and the Hopkins Symptom Checklist. The percentage of participants who scored positively for symptoms of PTSD depression and anxiety were 32.5%, 35% and 37.5%, respectively. Criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A comparison can be drawn from public health studies on Mexican drug crackdown-related violence. In one study where 40% of participants reported having witnessed a killing or a dead body as a traumatic trigger, approximately one third of them were diagnosed with PTSD, depression, and anxiety (O'Connor et al, 2014). Most witnesses were Mexican journalists covering the incidents, 35% of whom experienced PTSD (Flores Morales et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison can be drawn from public health studies on Mexican drug crackdown-related violence. In one study where 40% of participants reported having witnessed a killing or a dead body as a traumatic trigger, approximately one third of them were diagnosed with PTSD, depression, and anxiety (O'Connor et al, 2014). Most witnesses were Mexican journalists covering the incidents, 35% of whom experienced PTSD (Flores Morales et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are bereaved and/or have witnessed homicide are at risk of developing complicated grief, PTSD, and other mental health disorders (Rheingold & Williams, 2015; van Denderen et al, 2016). In Mexico, for example, over 30% of young adults living on the border experience anxiety and depression due to ongoing drug crackdown-related violence (O’Connor et al, 2014). In the Philippines, about one in five DRK incidents have occurred in or near the homes of victims, which has increased the risk of family members bearing direct witness to such tragedies (Atun et al, 2019).…”
mentioning
confidence: 99%
“…The situation became so dangerous that the Citizen's Medical Committee of Ciudad Juarez suggested employing military medics, already accustomed to war, to provide care in the city, instead of civilian doctors (Reforma Staff, 2011c). The lack of security during the worst years of the Mexican conflict severely disrupted the provision of even the most basic services as the community became very chaotic, and citizens felt confined to their homes because of the danger outside (K. O'Connor, 2014;K. O'Connor, Vizcaino, & Benavides, 2013).…”
Section: Contextmentioning
confidence: 99%